Methodik eines holistischen Variantenmanagements modularer Produktfamilien - Grundlagen, Systematik und beispielhafte Anwendung der VMahead Methodik - Weiser, Ann-Katrin (Reihe Informationsmanagement im Engineering Karlsruhe / Hrsg.: Karlsruher Institut für Technologie, Institut für Informationsmanagement im Ingenieurwesen (IMI), 2018)
A prominent solution to control a company's internal complexity is a modular product architecture. The implementation of a modular structure comes with high effort and cost. During the application phase these expenditures are compensated. However, a modular structure does not remain stable throughout its lifetime. Decisions on new modules have to be made. Therefore, a new method to support variant decisions on module, module variant and product level has been designed.